Hybrid Approach for product Recommendations using Collaborative filtering - Puranik, Chinmay; Otari, Grantej (International Journal of Computer Sciences and Engineering, 2019)
a successful recommendation approach in data mining can be done with the use of Collaborative Filtering (CF). It deals with the information which is recommended by people. People’s Choice is one of the better aspects of future recommendations. Typically, CF methods are mostly used for solving the problem of data sparsity and cold-start problem. A novel Domain-sensitive Recommendation (DsRec) is an algorithm used for the rating prediction by exploring the user-item subgroup analysis simultaneously. The Proposed work is an extension to DsRec using Trust-based system that considers the trust of the recommender. This type of recommendation system can help to get the information of user’s preferences in different types of domains which make rating predictions trust-worthy and efficient. A trust-based recommendation is complementing the developed algorithm.